Thermal analysis of three-phase induction motor - Lin, Chenqing. (2009)
Wind power contributes to a portion of renewable energies. Its technology has improved tremendously over the past decades. The demand for wind turbines has greatly increased as well. The aim of the study was to perform an analysis on a three-phase induction motor’s heat dissipation, which is applicable to a wind turbine generator. Three-phase induction motor was used for a small-scaled analysis. The operation and performance of such a device was examined through experimentation. Resistances of the three main heat sources were obtained. Thermal network diagram was constructed to understand the main heat flow path of the system. The diagram showed temperatures and heat dissipated at different points. It is found that frictional loss due to rotational effect was accounted for. To validate the theoretical analysis, experiments were performed. Only selective heat dissipation component’s temperatures were measured. The temperatures were generally lower when recorded at low, medium and high loading. Experimental and theoretical results were compared with a small percentage of error. The heat path of the components to the ambient surrounding was shown. This analysis when applied to the actual-sized equipment would exhibit a jump in the failure and maintenance frequency. Hence, it is critical that the heat dissipation within the motor is tackled effectively.